DAMPAK SUBSIDI LANGSUNG TUNAI (BLT)- BBM PADA KESEJAHTERAAN KELUARGA MISKIN DI BOGOR, JAWA BARAT - Puspitawati, Herien; Herawati, Tin; Sarma, Ma'mun (Jurnal Ilmu Keluarga dan Konsumen, 2008)
The aim of this study was to analyze the conditions of the family who received the SLT-BBM Program regarding on the income and expenditure and intra-household analysis. The study was conducted at Bogor City (Sub-District of West Bogor and South Bogor) and Bogor District (Sub-District of Ciomas), West Java Province. The study implemented a survey design through the process of purposive sampling procedures. One of the criteria of the study location was the location that had the highest quantity of poor families. The samples of the family were chosen purposively from the chosen location. The total of sample was 168 families (112 families who have men as the head of the household, and 56 families who have women as the head of the household). The study used descriptive analysis that contains of observations, secondary data, news, primary data (from questionnaire), in-depth interview and focus group discussion. The results found out that around half of the samples were actually not eligible to receive the program. Around 60% of the family had monthly income per capita of Rp 100,000.00 which was below the poverty line. The study also found out that in general, every household expended around 60% of the money for food (staple food) fulfillment. Then, the money received from the program was expended by family less then a week.